Análise comparativa de aplicativos mobile para o ensino da matemática para alunos do ensino fundamental - LIMA, Eduardo Garcia de (2024)
This study aimed to compare four applications for teaching mathematics, aiming to identify their main characteristics and point out their potentialities and limitations in the learning process of students. The methodology used was a descriptive and comparative analysis of the selected applications, considering criteria such as content, interface, interactivity, and didactic resources. The results showed that the applications present different pedagogical approaches and technical characteristics, which can directly influence students' learning. It was possible to verify that some applications have a greater variety of didactic resources, while others stand out for ease of use and interactivity. Based on these results, it is concluded that the choice of the most suitable application for teaching mathematics should take into account the characteristics of the class and pedagogical objectives, as well as the limitations and potentialities of each evaluated application. The research contributed to expanding knowledge about the possibilities of using applications for teaching mathematics and can support the decision-making of teachers and educational managers in choosing the most appropriate technological resources for their students.